Immunotherapy and radiotherapy in melanoma: a multidisciplinary comprehensive review. Issue 3 (31st May 2022) - Tagliaferri, Luca; Lancellotta, Valentina; Fionda, Bruno; Mangoni, Monica; Casà, Calogero; Di Stefani, Alessandro; Pagliara, Monica Maria; D'Aviero, Andrea; Schinzari, Giovanni; Chiesa, Silvia; Mazzarella, Ciro; Manfrida, Stefania; et al.
ABSTRACT: Melanoma is an extremely aggressive tumor and is considered to be an extremely immunogenic tumor because compared to other cancers it usually presents a well-expressed lymphoid infiltration. The aim of this paper is to perform a multidisciplinary comprehensive review of the evidence available about the combination of radiotherapy and immunotherapy for melanoma. Radiation, in fact, can increase tumor antigens visibility and promote priming of T cells but can also exert immunosuppressive action on tumor microenvironment. Combining radiotherapy with immunotherapy provides an opportunity to increase immunostimulatory potential of radiation. We therefore provide the latest clinical evidence about radiobiological rationale, radiotherapy techniques, timing, and role both in advanced and systemic disease (with a special focus on ocular melanoma and brain, liver, and bone metastases) with a particular attention also in geriatric patients. The combination of immunotherapy and radiotherapy seems to be a safe therapeutic option, supported by a clear biological rationale, even though the available data confirm that radiotherapy is employed more for metastatic than for non-metastatic disease. Such a combination shows promising results in terms of survival outcomes; however, further studies, hopefully prospective, are needed to confirm such evidence.